Implementasi Black Box Testing dan Usability Testing pada Website Sekolah MI Miftahul Ulum Warugunung Surabaya - Muhammad Taufik Abdillah; Ima Kurniastuti; Fajar Annas Susanto; Firman Yudianto (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2023)
In this study, system testing was carried out in the form of a school website at MI Miaftahul Ulum Warugunung Surabaya using black box testing and usability testing methods. The black box testing method focuses on functional testing of the system. The usability testing method focuses on user satisfaction with the experience of using the system. The usability testing method uses the USE Questionnaire which consists of four dimensions including usefulness, ease of use, ease of learning, and satisfaction. The results of black box testing show that of the 30 system features tested, all features have been successful following the expected results. Usability testing produces a usability value of 0.90 with a value close to 1 so that the website is a good information system.